Transduction of interleukin-2 antiapoptotic and proliferative signals via Akt protein kinase - Ahmed, Naheed N. (The National Academy of Sciences of the USA, 1997)
The interleukin-2 (IL-2) receptor (IL-2R) is composed of three subunits. Of these, IL-2Rα is required for high-affinity IL-2 binding, while IL-2Rβ and IL-2Rγ(c) are required for the transduction of IL-2-generated signals. Signals transduced via the S region of the IL-2Rβ (amino acids 267–322) in BAF/3 cells activate the phosphatidylinositol 3-kinase (PI3-kinase) and induce the expression of Bcl-2 and c-myc. Through the induction of Bcl-2, IL-2 inhibits apoptosis and through the combination of Bcl-2 and c-myc it stimulates progression through the cell cycle. Here we show that the protein kinase encoded by the Akt proto-oncogene is activated by IL-2. Akt activation by IL-2 depends on PI3-kinase signals transduced via the S region of the IL-2Rβ and is linked to the translocation of Akt to the cell membrane. Expression of catalytically active Akt mutants in BAF/3 cells expressing IL-2Rβ[A0]ΔS promotes the expression of Bcl-2 and c-myc, inhibits apoptosis induced by IL-3 deprivation or staurosporine, and stimulates cell cycle progression. The same mutants also stimulate cell cycle progression in 2780a, an IL-2-dependent T cell line that undergoes G(1) arrest rather than apoptosis after IL-2 deprivation. The activation of Akt by IL-2 via the PI3-kinase and the rescue of the PI3-kinase-mediated antiapoptotic and proliferative IL-2 signals by catalytically active Akt indicate that these signals are transduced by Akt.